An analysis of the role and mandate of the motor industry ombudsman of South Africa under Consumer Protection Act 68 of 2008 - Magau, Phemelo (University of Pretoria, 2024)
Mini Dissertation (LLM (Consumer protection law))--University of Pretoria, 2023.